Using inflammatory indices for assessing malnutrition among COVID-19 patients: A single-center retrospective study - Buthaina Alkhatib; Huda M. Al Hourani; Islam Al-Shami (Elsevier, 2022)
Background: Coronavirus disease 2019 (COVID-19) causes malnutrition in infected patients. This study aimed to investigate the use of systemic immune-inflammatory index (SII), platelet-to-lymphocyte ratio (PLR), the Glasgow Prognostic Score (GPS), and neutrophil-to-lymphocyte ratio (NLR) for malnutrition assessment among COVID-19 inpatients. Methods: This is a single-center retrospective study on 108 hospitalized COVID-19 patients; 14 were admitted to the intensive care unit (ICU). Data were collected from patients' profiles while NLR, PLR, GPS, and SII were calculated. Inflammatory indices' predictive power was analyzed using the receiver operating characteristic curve (ROC). A P-value of < 0.05 was considered statistically significant. Results: Hospitalization days, neutrophils count, C-reactive protein (CRP), and serum urea levels were significantly higher in ICU patients. None of SII, PLR, and NLR were significantly different between ICU and non-ICU groups. Also, albumin and GPS showed a higher sensitivity level (100.0), followed by PLR and SII (78.57 and 71.34, respectively). Regarding ROC curves, even though NLR, PLR, and SII provided the largest area under the curve (AUC) (0.687, 0.682, 0.645; respectively), they have shown a poor discrimination ability, while GPS and albumin were ineffective in predicting malnutrition in COVID-19 patients. Conclusion: NLR, SII, and PLR showed poor predicting ability for malnutrition among COVID-19 inpatients. Additional consideration should be taken for using inflammatory parameters (SII, PLR, GPS, and NLR) to predict malnutrition in COVID-19 inpatients.